2021
DOI: 10.1002/admi.202100174
|View full text |Cite
|
Sign up to set email alerts
|

Directional Metastable Wetting Evolution of Droplets on Artificial Patterned Microcavity Surfaces

Abstract: Controllable wetting transition on artificial microtextured surfaces has significant applications in many industrial fields. In this work, the droplet spreading and the directional wetting transition are investigated on the substrate surface with the patterned microcavities. The results show that the macroscopic inward wetting transition from the periphery to the center of the droplet strongly depends on the mesoscopic sequential transition from Cassie to Wenzel state in the microcavities on the substrate surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Typical examples are shown in refs. [99][100][101][102][103][104]. For instance, Liu et al [99] adopted a doubly reentrant structure that enables very low liquid-solid contact fraction which make the surface repel any liquid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical examples are shown in refs. [99][100][101][102][103][104]. For instance, Liu et al [99] adopted a doubly reentrant structure that enables very low liquid-solid contact fraction which make the surface repel any liquid.…”
Section: Introductionmentioning
confidence: 99%
“…This result has potential application for the drag reduction of submerged surfaces. Xu et al [103] investigated the droplet spreading and wetting transition on the microcavitypatterned substrate. This work showed that the mesoscopic sequential Cassie-Wenzel transition leads to the macroscopic inward wetting transition from the periphery to the droplet center.…”
Section: Introductionmentioning
confidence: 99%